Measurement of uhf signal propagation loss under different altitude in hilly environment - Elshafie, H. (2013)
In this paper, the effect of environment and altitude on ultrahigh frequency (UHF) band has been studied. Both theoretical study and experimental investigations are conducted in order to model and characterize such complex communication medium. The experimental study is primarily aimed at critically analyzing the detrimental impact of channel condition on received power in hilly environment under different altitudes. The propagated signal strength varies from one place to another due to time varying channel condition as a result of obstacles between the transmitter and receiver. There is dramatic need to experimentally investigate such scenario in order to provide an avenue through which service providers can strategies their policies for effective wireless communication. Developing such channel models is extremely useful in communication systems design and simulation. The proposed model has been compared with ITU-R model for verification of the develop model for propagation loss prediction in hilly environment. The results obtained are compared with different measurement at various altitudes in hilly terrain environment.